2003
DOI: 10.1007/s00464-002-8911-x
|View full text |Cite
|
Sign up to set email alerts
|

A prospective single-blinded controlled study comparing laparoscopic ultrasound of the common bile duct with operative cholangiography

Abstract: Laparoscopic ultrasound examination of the bile duct is superior to operative cholangiography and could replace it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 14 publications
4
32
0
2
Order By: Relevance
“…Moreover, it does not require new X-ray apparatus, radiologists, or laboratory technicians. Many studies, including two randomized control trials, have reported that visualization of the biliary tract anatomy and diagnostic performance of IOUS for bile duct stones are as high, or better, than those for cholangiography [17,[21][22][23] . It has also been reported that IOUS decreases the necessity to perform cholangiography [29,30] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it does not require new X-ray apparatus, radiologists, or laboratory technicians. Many studies, including two randomized control trials, have reported that visualization of the biliary tract anatomy and diagnostic performance of IOUS for bile duct stones are as high, or better, than those for cholangiography [17,[21][22][23] . It has also been reported that IOUS decreases the necessity to perform cholangiography [29,30] .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, IOUS requires a shorter examination time [17][18][19] , is safe without incurring radiation exposure, www.wjgnet.com and is minimally invasive [18,20] . It has been reported that IOUS allows for visualization equal to or better than that of cholangiography [17,[20][21][22][23] in the case of biliary anatomy and diagnosis of bile duct stones. However, there have been few studies that have investigated whether the routine implementation of IOUS decreases BDI during LC [24] .…”
Section: Introductionmentioning
confidence: 99%
“…Die laparoskopische Sonographie erreicht mit einer Spezifität von bis zu 100% bei einer Sensitivität von 96% ähnlich gute Ergebnisse wie die IOC bei der Diagnostik der Choledocholithiasis [11] [12]. Mit Ablösung der offenen Cholezystektomie als Standardverfahren bei der Cholezystektomie ist die Debatte über die notwendige intraoperative Gallengangsdarstellung mittels Cholangiographie oder Sonographie fortgesetzt worden.…”
Section: Intraoperative Abklärungunclassified
“…In an attempt to try and demonstrate one method superior to the other, Aziz et al [14] performed a meta-analysis including 11 studies whose results demonstrated no significant difference in either sensitivity or specificity between each method. However, more recent studies have been able to demonstrate a higher specificity, in some cases nearly 100%, using laparoscopic ultrasound [15] . Additional advantages to LUS include that it is efficient, does not require cannulating the biliary system, and it can be accomplished prior to a complete and sometimes tedious dissection as it is easily repeated as needed during the course of an operation.…”
Section: The Dichotomy Of Biliary Duct Imaging In Acute Cholecystitismentioning
confidence: 99%
“…Additional advantages to LUS include that it is efficient, does not require cannulating the biliary system, and it can be accomplished prior to a complete and sometimes tedious dissection as it is easily repeated as needed during the course of an operation. Furthermore, LUS does not require fluoroscopy, and it has a lower failure rate than IOC, being extremely useful in defining the hepaticoduodenal anatomy [15][16][17] . In spite of these many benefits, LUS is rarely taught and rarely utilized in practice because of the technique's large learning curve and the traditional acceptance of IOC as best care.…”
Section: The Dichotomy Of Biliary Duct Imaging In Acute Cholecystitismentioning
confidence: 99%